The Erythrina Protease Inhibitor: Interactions with Tissue Plasminogen Activator - Heussen-Schemmer, Christa; Merrifield, Edwin H; Dowdle, Eugene B D (Thrombosis and Haemostasis, 1991)
The Kunitz-type trypsin and tissue plasminogen activator (t-PA)-inhibitor from Erythrina caffra seeds was cleaved by trypsin at low pH to yield a disulphide linked two-chain molecule with reduced hydrophobicity. This change was used to separate cleaved from native inhibitor by phenyl-Sepharose chromatography. The inhibitor was not cleaved by t-PA. Trypsin, but not t-PA, catalysed resynthesis of the cleaved bond.Although the cleaved protein retained inhibitory activity for both trypsin and t-PA, 6-10 times higher concentrations were required for equivalent inhibition.Removal of the active site arginine (Arg63) from the cleaved inhibitor by digestion with carboxypeptidase B resulted in a further loss of inhibitory activity towards both proteases. The activity of the inhibitor could also be decreased by modification of one susceptible arginine residue with peptidyl arginine deiminase. These results suggest that the trypsin-reactive site of the Erythrina inhibitor is also involved in the interaction between the inhibitor and t-PA.